If a x = b y = c z and a 3 = b 2 c , with x , y , z are non zero numbers, and a , b , c are positive non-one numbers.
What is the value of x 3 − y 2 ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Hehe, Easy problem. And Perfect Solution! :)
That's right the unification of symbols is the method :)
If we assume that a , b , c are positive reals, then if we take the common logs of the given equations we find that
x lo g ( a ) = y lo g ( b ) = z lo g ( c ) and 3 lo g ( a ) = 2 lo g ( b ) + lo g ( c ) .
From the first of these we see that lo g ( c ) = z y lo g ( b ) , and so if we also assume that none of a , b , c equal 1 we find that
x lo g ( a ) 3 lo g ( a ) = y lo g ( b ) 2 lo g ( b ) + z y lo g ( b ) ⟹ x 3 = y 2 + z y = y 2 + z 1 ⟹ x 3 − y 2 = z 1 .
If a^x=b^y=c^z, then we can say that a^x a^x=b^y c^z a^2x=b^y c^z Compare this to a^3=b^2 c Hence, 2x=3, y=2, and z=1 x=3/2 Substitute these values into the equation into (3/x-2/y) If we do this, we arrive at the answer 2-1=1. Now we need to choose the answer choice that will get us to 1. Since z=1, 1/z=1 as well, so the answer is 1/z.
Problem Loading...
Note Loading...
Set Loading...
Let, a x = b y = c z = k Then a = k x 1 , b = k y 1 , c = k z 1 Put the value of a , b , c in the given relation a 3 = b 2 c we get, k x 3 = k y 2 k z 1 or, k ( x 3 − y 2 ) = k z 1 hence ( x 3 − y 2 ) = z 1